2015
DOI: 10.1093/ejcts/ezu537
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of the subvalvular apparatus during mitral valve replacement of rheumatic valves does not affect long-term survival

Abstract: Patients submitted to MVR for rheumatic mitral valve disease have a poor prognosis, independently of having the subvalvular apparatus preserved. PSVA did not improve late survival in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…Patient‐related factors which predispose to LVOT obstruction include an intrinsically small LVOT, as occurs in patients with septal hypertrophy, sigmoid‐shaped septum, or small LV cavity size. The last is especially common in the elderly and those with mitral stenosis …”
Section: Discussionmentioning
confidence: 99%
“…Patient‐related factors which predispose to LVOT obstruction include an intrinsically small LVOT, as occurs in patients with septal hypertrophy, sigmoid‐shaped septum, or small LV cavity size. The last is especially common in the elderly and those with mitral stenosis …”
Section: Discussionmentioning
confidence: 99%
“…Coutinho et al have already identified pure mitral regurgitation as one of the independent risk factors for late mortality. 28 Okita et al compared three patient groups that underwent either MVR with chordal preservation, conventional MVR or OMC due to pure mitral stenosis. 24 There were no differences between the groups in terms of mitral valve area, cardiac index, LV end-diastolic and end-systolic volume index and contractility index in the early postoperative period; However, LV EF showed a significant increase in the chordal preservation and OMC groups and a slight decrease in the conventional MVR group.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from anecdotal reports, there are few data to guide treatment of LVOT obstruction due to bioprosthetic malposition. In symptomatic patients, treatment may require valve re‐replacement . Successful outcomes have also been reported following alcohol septal ablation .…”
Section: Lvot Obstruction Following Surgical Mitral Valve Replacementmentioning
confidence: 99%